Effectiveness of the Kids in Control of Food (KICk–OFF) structured education course for 11–16 year olds with Type 1 diabetes. Issue 2 (9th September 2015) - Price, K. J.; Knowles, J. A.; Fox, M.; Wales, J. K. H.; Heller, S.; Eiser, C.; Freeman, J. V.
Abstract: Aim: To assess the effect of a 5–day structured education course (Kids in Control of Food; KICk–OFF) on biomedical and psychological outcomes in young people with Type 1 diabetes. Methods: This was a cluster‐randomized trial involving 31 UK paediatric centres. Participants were recruited prior to stratified centre randomization. Intervention centres delivered KICk–OFF courses, whereas control centres delivered usual care. Participants were 11–16 years of age and had Type 1 diabetes for at least one year. The KICk–OFF course was delivered by trained educators to eight participants per course. Glycaemic control and quality of life were measured at baseline, 6, 12 and 24 months. Secondary outcomes were hypoglycaemia, ketoacidosis, fear of hypoglycaemia and diabetes self‐efficacy. Results: Three hundred and ninety‐six participants provided baseline data (199 intervention and 197 control). At 6 and 12 months the intervention group showed significantly improved total generic quality of life scores compared with controls (baseline: 80 vs. 82; 6 months: 82 vs. 82; P  = 0.04). Across the whole intervention group mean HbA1c levels were not significantly different from controls; baseline HbA1c mean (95% confidence interval), 78 mmol/mol (75–81) vs. 76 mmol/mol (74–79) [9.3% (9–9.6%) vs. 9.1% (8.9–9.4%); 24 months: 77 mmol/mol (74–79) vs. 78 mmol/mol (75–81) (9.2% (8.9–9.4%) vs. 9.3% (9–9.6%)], adjusted mean difference, –2.0 mmol/mol (6.5–2.5) [2.3% (–2.7% to 2.4%)], P  = 0.38. Conclusions: Attending a KICk–OFF course was associated with significantly improved total quality of life scores within 6 months. Glycaemic control, as measured by HbA1c, was no different at 24 months. (Clinical Trial Registry No: ISRCTN3704268) What's new?: KICk–OFF is based on the Dose Adjustment For Normal Eating (DAFNE) programme which is widely available to adults in the NHS. There are no validated courses for children and young people. The KICk–OFF study is the first randomized controlled trial of intensive structured education in adolescents with Type 1 diabetes. Although recruitment to the study was a challenge, retention within the 5–day course was very good suggesting that it is possible to engage this age group in intensive group education. National audits have shown that there is a large UK cohort of young people who would potentially benefit from participation in a KICk–OFF course.